New look, new TRP! - AJP, Editor (Asian Journal of Pharmaceutics (AJP), 2014)
Effective July 1, 2008 AJP has become open access. It is now on free submission and free download basis. New look on the web, as well as on print, has made the journal a hot item. Today (July 25, 2008, 11:20 am), as I am writing this editorial, site statistics indicate that in the last 25 days, Volume 2(1) has already been viewed 10648 times with Orodispersible Tablets: An Overview; by Suresh Bandari, Rajendar Kumar Mittapalli, Ramesh Gannu, Yamsani Madhusudan Rao toping the tally with score of 1803. It is customary to rate the scientific journal on the basis of impact factor (IF); however till such time the IF becomes available to AJP, we can rely on target (not television) rating point (TRP). Although we are in the process of putting special recognition/reward for the authors and referees of the articles that have high quality and generate high traffic, till that time let the viewed score be the sole basis of rating any article. Hence, all are requested to keep looking the site statistics to make assessment of the knowledge that either you contributed to the journal or are taking from.